POLITICAL LEADERSHIP AS A DETERMINATIVE FACTOR AND VOTER BEHAVIOR: AN AREA RESEARCH ON THE PROVINCE OF KARAMAN (IN TURKEY) LOCAL ELECTION RESULTS - OKUR ÇAKICI, Fatma; DOĞANAY, Taylan Can (SSD Journal, 2019)
The leader as a word is Anglo Saxon origin. İn the 10th century, it had been derived from the laudan word. At that time the leader had beed used to meaning of travelling and causing travel. Esspecially the word causing draws attention. Afterward, the leader expressed the meaning of the Pioneer in the 14th century. As seen the context of the word’s origin includes social and economi causes which eafected the long voyages and discoveries. But, the leader word which turned into using pejorative about that different behaviors of the subclasses which exclude norms in the 15th and 16th centuries, reached its conceptual quality during the perionds of political and social crisis in the 20th century. Especially, the organized masses and charismatic political leader of the right-wing ideologies which been powerful in Europe, has established the leadership in the religious and political context. Thence, leadership as a phenomenon has been considered worthy investigated since 20th century.On the other hand political leadership is the role which has by the individuals who are affect important political consequences in the political world, undertake unexpectedly important social and political responsibilities and have personal styles/characteristcs and trends. In this aspect that political leadership is always created by every situation in which exist hierarchy. In this study, political leadership is seen as a determining factor which effect on the voter behavior. And through the theoretical approach that political leadership effect on the voter behavior, Winter’s triple model depicts three dimensions these are leader appeal, leader and situation matching, leader and voter/follwer matching. a) According to leader appeal, the successful leader has certain personal characteristics such as energy, determination, charisma and shares this features with the social environment. b) Leader and situation matching assume that successful leader’s characteristics is the optimal for the political context. c) Leader and voter matching assume that the successful leader’s characteristics as a stimulant effect are consistent with voters’ perception. This study, research has focused on Turkey’s Local Election 2019 Results in Karaman city during research. All neighborhoods in the city center of Karaman (63 neighborhoods) were defined as the site of study. The sample was considered as wide as possible. However, 33% of the target population of 400 people had could be able accepted the source of healthy raw data. The survey as a data acquisition technique was used for the target population and structured questions and openended questions were asked questions to get data. Finally, the descriptive statistic were apply by using SPSS program in the analysis of the obtained data.